Hannibal at the gates: Cyberwarfare & the Solarwinds sunburst hack. Issue 2 (4th October 2022) - Datta, Pratim
The connected world economy, compounded by the COVID-19 pandemic, has forced countries, companies, and organizations to pivot to digitally transforming their operations. Sophisticated, state-sponsored perpetrators have seized this forced pivot to lay the groundwork for Cyberwarfare with Advanced Persistent Threats. Using the 2020 Solarwinds Orion Sunburst hack campaign, this research uses a grounded case study approach to highlight the facets of the Sunburst cyberwarfare campaign. Findings suggest that cyberwarfare underscores the need for revisiting organizational processes, culture, and paradigms that are capitalized and leveraged by state-sponsored perpetrators. The Sunburst hack prompted organizations to immediately assume technical solutions. Among them, organizations were quick to isolate infected assets and patch infected systems. However, this research argues that such a reactive technical fix is a vicious trend based on a "wait, watch, react" ideology. Instead, there is prima facie need for process reengineering organizational operations and cultures to build and maintain preventive readiness.